2009
DOI: 10.1021/la8037704
|View full text |Cite
|
Sign up to set email alerts
|

Pinning, Retraction, and Terracing of Evaporating Droplets Containing Nanoparticles

Abstract: We consider the dynamics of a slender, evaporating droplet containing nanoparticles. We use lubrication theory to derive a coupled system of equations that govern the film thickness and the concentration of nanoparticles. These equations account for capillarity, Marangoni stresses, evaporation and disjoining pressure; the nanoparticles-induced structural component of the disjoining pressure is also considered. Contact line singularities are avoided through the adsorption of ultrathin films wherein evaporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
106
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 61 publications
(152 reference statements)
3
106
0
Order By: Relevance
“…This interest is driven by many technological and biological applications, e.g. the evaporation of blood serum drops has recently been introduced as a diagnostic tool for certain diseases (5) , Craster et al have proposed the use of drying droplets for nanopatterning deposition (6) and Dugas et al have proposed its use in DNA stretching (7) .…”
Section: Introductionmentioning
confidence: 99%
“…This interest is driven by many technological and biological applications, e.g. the evaporation of blood serum drops has recently been introduced as a diagnostic tool for certain diseases (5) , Craster et al have proposed the use of drying droplets for nanopatterning deposition (6) and Dugas et al have proposed its use in DNA stretching (7) .…”
Section: Introductionmentioning
confidence: 99%
“…In a separated study, the evaporating droplets containing nanoparticles were studied theoretically based on the lubrication theory, by deriving a system of equations that govern the film thickness and concentration of nanoparticles [21].…”
Section: Effect Of Nanoparticles On the Behavior Of Triple Linementioning
confidence: 99%
“…The modification of the effective thermophysical properties influences the pressure drop and heat transfer coefficient in macro/microchannels [2]. The modification of liquid-gas and solid surface tensions would change the force balance at the triple line and consequently affect its dynamic behavior [7][8] including the radius of triple line [9] and the bubble contact angle [5,10], which has significant effects on the bubble growth and departure process [11][12][13][14][15][16], as well as the boiling heat transfer [6,[17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that evaporative flux is not diverging at the three phase contact line, but still has a maximum over there. Craster et al [9] demonstrated also a variety of different behaviours of the system in question: spreading, retraction, contact line pinning, and "terrace" formation.…”
Section: Introductionmentioning
confidence: 99%
“…Craster et al [9] studied evaporation of sessile droplets to ambient vapour. They used kinetic model of evaporation.…”
Section: Introductionmentioning
confidence: 99%